Descripción de los factores de riesgo para recaída en pacientes con diagnóstico de trastorno mental (2011)
Objective: The objective of this paper is to describe the population served in mental health institutionsfor mental illness relapse, and the process of identifying risk factors in relapsing patientsdiagnosed with severe mental illness. To this end a descriptive exploratory multicenter, multistageepidemiological study was carried out in mental health institutions of the Order of San Juan deDios Hospital (OHSJD) with hospitalized relapsing patients with a diagnosis of severe mentaldisorder. This study comes from a working network of Psychology professionals in the OHSJDnationwide. Materials and methods: The population sample was of 1005 patients diagnosed withsevere mental disorders, who had presented relapse during the last year. First, the characterizationof the general population was conducted; then, it was narrowed down to the centers, taking intoaccount similarities and differences found according to the clinical and demographic variables.Results: Major risk factors for relapse found in patients diagnosed with severe mental disorderswere: having between 38 and 58 years of age, being female, single, graduates, unemployed, witha prevalence of bipolar affective disorder diagnosis, number of hospitalizations between 2 and10, number of drugs at the time of leaving hospital 2 to 6, with severe difficulties relating withothers and difficulties in adherence to treatment. The need for a caregiver was also found, as wellas a limited number of received psychological interventions. How the system of beliefs affects thedisease and the poor adherence to treatment was identified. Conclusions: These results indicatethe requirement of a design of team intervention strategies, ranging from the assessment team(home), definition of therapeutic action plans (for) and the posthospitalizacion (egress) following.There is a poor support network and limited adherence to comprehensive treatment.